The COVID-19 Pandemic and the Movement of the Bisnis-27 Stock Index from January to December 2021 - Shintia, Deny; Hadistya, Istifar Dilla; Hardika, Mutia (Research in Accounting Journal (RAJ), 2023)
The COVID-19 pandemic in Indonesia has also impacted the capital market, leading to changes in trading hours on the Indonesia Stock Exchange. This situation served as a negative signal for investors, prompting many to sell their shareholdings. The results of this study indicate that an increase in the number of confirmed positive COVID-19 cases negatively affects the movement of the Bisnis-27 stock index. Similarly, the number of COVID-19-related deaths also has an impact on the index. However, the number of fully vaccinated individuals does not significantly influence the Bisnis-27 index. Therefore, it is strongly recommended that investors take into account the rising number of positive COVID-19 cases and related fatalities when making investment decisions in companies listed on the Bisnis-27 index.